Gaining sustainable competitive advantage through human capital: Does firm specific human capital or general human capital matter? - Ibrahim, Muhammad Garba; Abdullah, Haim Hilman (Academy for Global Business Advancement (AGBA), 2015)
The highly competitive atmosphere In which organizations operate today, achieving and sustaining competitive advantage is increasingly becoming the central theme for firm‘s survival (Flint & Golicic, 2009).Specifically, recent trend of knowledge based economy has question the traditional method of utilizing only financial and other tangible resource may not provide sustainable competitive advantage for organizations (Lan, Lu, & Chen, 2013). The role of organizations human capital resource is increasingly becoming imperative in the successful implementation of organizations policies and activities aimed at ensuring competitiveness in the marketplace (Díaz-Fernández, López-Cabrales, & Valle-Cabrera, 2014).By implication, firm‘s economic activities are undergoing a paradigm shift towards knowledge and intellectual based dimension.This development makes knowledge asset replace and take the lead among other production factors available to business firms (Delgado-Verde, Martín-de-Castro, Navas-López, & Cruz-González, 2011).In addition, strategy and human resource management literature has long proposed human capital as important element that enhances firm‘s performance and long term profit in knowledge based economy (Hsu & Fang, 2009). This resource is developed and maintained in organizations human resource and it is highly movable within the factor market (Sydler, Haefliger, & Pruksa, 2014). This is because human resource with large stock of human capital can easily quit their current job if it does not meet their requirement (Teece, Pisano, & Shuen, 1997). The tendency of human capital mobility has shifted attention of scholars to focus on development of firm specific human capital (Barney, 1991; Wright, 1992).In line with resource based view perspective, Penrose, (1959) posit that firms can gain competitive advantage based on two basic pillars i.e. firms resource heterogeneity and firms resource immobility.This prompt contribution from other scholars such as Barney (1991), where he introduced value, rarity, inimitability and non-substitutability as not only requirement but necessary conditions for sustainable competitive advantage. Moreover, as studies in human resource and strategic human resource management lean toward investigating and advocating for internal resource utilization through unique human capital configuration, little is known about the most suitable level at which this resource can be developed. In addition, understanding human capital development through general or firm specific skills has recently become debatable.These suggest that, the appropriate strategy still remain vague.Therefore in this paper we review relevant literature focusing on human capital. We argue that both firm specific and general human capital depend on a given firms‘ situation.